2000
DOI: 10.1128/jb.182.6.1748-1753.2000
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Is Involved in Environmental Stress Responses in Rhizobium tropici , Including Acid Tolerance

Abstract: The isolation of rhizobial strains which exhibit an intrinsic tolerance to acidic conditions has been reported and has facilitated studies on the basic mechanisms underlying acid tolerance. Rhizobium tropici strain CIAT899 displays a high intrinsic tolerance to acidity and therefore was used in this work to study the molecular basis of bacterial responses to acid conditions and other environmental stresses. We generated a collection of R. tropici CIAT899 mutants affected in acid tolerance using Tn5-luxAB mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 46 publications
(31 reference statements)
2
60
0
3
Order By: Relevance
“…The authors suggested that glutathione may play a role in the regulation of catalases, possibly through its regulation of intracellular H 2 O 2 or through its interaction with redox-sensitive sites in the OxyR regulatory protein. GSHdeficient yeast mutants, as well as R. tropici gshB mutants, showed dramatic sensitivity to H 2 O 2 (12,24). Altogether, these data suggest that GSH and catalases provide overlapping defenses for protection against H 2 O 2 in both prokaryotic and eukaryotic cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The authors suggested that glutathione may play a role in the regulation of catalases, possibly through its regulation of intracellular H 2 O 2 or through its interaction with redox-sensitive sites in the OxyR regulatory protein. GSHdeficient yeast mutants, as well as R. tropici gshB mutants, showed dramatic sensitivity to H 2 O 2 (12,24). Altogether, these data suggest that GSH and catalases provide overlapping defenses for protection against H 2 O 2 in both prokaryotic and eukaryotic cells.…”
Section: Discussionmentioning
confidence: 48%
“…The emergence of nodules on M. sativa following inoculation with the mutant strain SmgshB was delayed in comparison to wt Rm1021, although the final nodule number was unaffected. Similarly, the number of nodules on Phaseolus vulgaris and Leucaena leucocephala 4 weeks postinoculation with the gshB-deficient strain was found to be similar to that on plants inoculated with the wild-type strain (24). A highly significant feature of our study was the large reduction in the nitrogen fixation capacity of nodules.…”
Section: Discussionmentioning
confidence: 50%
“…This mutant is sensitive to weak organic acids and to osmotic and oxidative stress, and the addition of GSH restores the responses to these stresses to wild-type levels. Interestingly, the mutant can form effective nodules on bean, but it is out competed by the wild-type strain, indicating that GSH is important for stress tolerance and the symbiotic process (Riccillo et al, 2000).…”
Section: Ascorbate Glutathione and Homoglutathione Are Major Antioxmentioning
confidence: 99%
“…The GSH may be internally consumed by bacteroids in metabolic reactions and maintenance of cellular redox status rather than being exported to the plant (Iturbe-Ormaetxe et al, 2001). Recently, a mutant of Rhizobium tropici has been isolated which is deficient in glutathione synthetase and contains only 3% of the GSH present in the wild-type strain (Riccillo et al, 2000). This mutant is sensitive to weak organic acids and to osmotic and oxidative stress, and the addition of GSH restores the responses to these stresses to wild-type levels.…”
Section: Ascorbate Glutathione and Homoglutathione Are Major Antioxmentioning
confidence: 99%
“…A number of genes required for the growth of rhizobia in low pH conditions have been identified (Goss et al, 1990;O'Hara et al, 1989;Riccillo et al, 2000;Tiwari et al, 1992;Vinuesa et al, 2003). Construction of mutants from the acid-tolerant strain Sinorhizobium medicae WSM419 has allowed the identification of some of the genes required in acidic conditions (Dilworth et al, 2001).…”
Section: Introductionmentioning
confidence: 99%